Research of the vacuum brake booster working process - Н. Скляров; А. Шаповалов; П. Черненко; А. Корнев; A. Кашканов; В. Кашканов; В. Кучерук (Қарағанды университетінің хабаршысы. Физика сериясы)
The creation of a laboratory installation was carried out with an aim to ensure the study of the working processes and characteristics of vacuum boosters as a part of hydraulic brake drives for vehicles with a gross weight of up to 3.5 tons for civilian usage, and armored vehicles with a gross weight of up to 8.5 tons designated for service and combat missions. Theoretical researches in this direction have been previously carried out by a number of scientists of the Department of “Automobiles” named after prof. Gredeskul A.B. in Kharkiv National Automobile and Road University, the results of which have been highlighted in a number of scientific papers. Comparison of the results of theoretical studies with the experimental ones, received on the laboratory setup and suggested in this paper, according to the experimental method described in the article, using the created electronic signal processing complex and sensor unit, made it possible to establish a discrepancy between theoretical and experimental studies within 6%. This complex for experimental research was created for the first time, thus allowing to obtain the results that confirm the theoretical studies of the vacuum boosters of the brake drive of cars, as well as revealed a number of dependencies between the weight and overall parameters of the under research unit, along with the number of functional relationships between the structural components of the vacuum boosters, which enables to significantly optimize its design.